The role of tenure documents for livelihood resilience in Trinidad and Tobago. (September 2019) - Daniel, Desiree; Sutherland, Michael; Ifejika Speranza, Chinwe
Highlights: The documentality concept is used to link land tenure and livelihood resilience. This article highlights the role of documents as material artefacts of institutions. We further discuss the dependence between documentation and resource access for resilience. With documentality, the focus shifts to the types of documents needed for resilience. Abstract: In this paper, we use the concept of documentality to explore the role of documentation of land tenure in the livelihood resilience of farmers in Trinidad and Tobago. We studied small-scale farmers whose livelihoods occur on lands held under different tenure arrangements. We found that it is not the access to land but the formal documentation of access to land that enables livelihood resilience. Not having tenure documentation excludes farmers from loans and state incentives for agriculture. This weakens the buffer capacity of the affected farmers, which is a contributor to livelihood resilience.